Customers’ Acceptance of Anti–Money Laundering Practices in Banks: Evidence from Kathmandu Valley (Quest Journal of Management and Social Sciences, 2025)
Background: Money laundering undermines financial transparency and stability by disguising illegally obtained funds and integrating them into the legitimate economy. Its growing complexity poses global and national risks, including in Nepal, where regulatory efforts face challenges in enforcement, technology, and public awareness.Purpose: This study analyzes the insights of customers within the Kathmandu Valley on banks' implementation of anti-money laundering practices.Design/methodology/approach: This study utilized an exploratory research design to investigate the subject matter. Non-probability sampling methods were employed to gather data, resulting in a total of 408 samples collected through Kobo Toolbox. The data analysis employed both descriptive and inferential techniques, with descriptive analysis providing an overview of the basic features of the data and inferential analysis facilitating broader conclusions. The analytical process was conducted using Excel for data management and SmartPLS 4.0 for structural equation modeling, enabling a thorough examination of the relationships between variables.Findings: The results indicate that customer awareness, discomfort, and trust have a significant influence on attitudes, which in turn strongly predict customer acceptance of AML practices. Mediation analysis further confirms that attitudes significantly mediate all three relationships, highlighting their central role in shaping AML compliance behavior.Conclusion: This study concludes that customers' awareness of money laundering and terrorism financing, their trust in banking secrecy measures, and their levels of discomfort with AML requirements all play significant roles in shaping their acceptance of banks' AML practices. Notably, the research emphasizes the role of attitude as a mediating factor in this relationship. Customers' attitudes influence how their awareness, trust, and discomfort translate into acceptance of AML practices.Key Words: Anti Money Laundering, Know your Customers, Banks, Awareness, Trust, Discomfort, Acceptance